Paradoxien in Migranten Organisationen: Über die unversöhnlichen Missionen der Kroatischen Mission - Goeke, Pascal (ERDKUNDE, 2007)
Self-organisations of migrants are usually assessed with regard to their contribution in the so-called process of integration. However, even similar organisations are sometimes considered as fostering and on occasion as lagging the process of integration. The question why these contradictory judgements occur is hardly addressed, although that paradox demands further explanation. With the example of the Catholic Croatian Mission it will be shown how self-organisations of migrants are constituted and which codes are used to differentiate between system and environment. In the context of demographic change and ongoing integration,multiple codings provoke controversies over the mission’s prospective path. The paradox becomes evident: terms of its success become at the same time terms of its failure. Serving the purpose of integration, the mission itself abrogates its own constitutional and legitimizing codes. Thus, it threatens the unity of the organisation.